Preliminary Studies on Suppression of Important Plant Pathogens by Using Pomegranate and Avocado Residual Peel and Seed Extracts - Stefanos Leontopoulos; Prodromos Skenderidis; Konstantinos Petrotos; Chrysanthi Mitsagga; Ioannis Giavasis (Horticulturae, 2022)
Potential synergistic action of aqueous extracts of pomegranate peel (PP), avocado peel (AP), and avocado seed (AS) wastes isolated by microwave-assisted extraction were assessed in in vitro and in vivo assays as biocontrol agents against several plant pathogenic fungi. The study findings contribute to the utilization of a value-added industrial byproduct and provide significant value in advancing the development of new plant protecting compositions that benefit from the synergistic effects between two important plant species that contain several natural bioactive compounds. More specifically, the in vitro results proved that the use of 100%-pure (PP) extracted waste affected the mycelium growth of Penicillium expansum. Furthermore, mycelium growth of Aspergillus niger was decreased by 10.21% compared to control after 7 days of growth in medium agar containing 100% AP and extracted waste. Moreover, mycelium growth of Botrytis cinerea was affected by equal volume of avocado extraction wastes (50% peel and 50% seed) only at the first 3 days of the inoculation, while at the seventh day of the inoculation there was no effect on the mycelium growth. Equal volumes of the examined wastes showed decreased mycelium growth of Fusarium oxysporum f.sp. lycopersici by 6%, while Rhizoctonia solani mycelium growth was found to be the most sensitive in PP application. In addition, the in vivo assay shown that PP extract suppresses damage of tomato plants caused by R. solani followed by extracted wastes from AP. Based on the research findings, it can be argued that PP and AP extracts can be used as natural antifungals instead of dangerous synthetic antifungals to effectively treat phytopathogens that cause fruit and vegetable losses during cultivation.